Biodegradation of 17α-ethynilestradiol Using a Mixed Culture Isolated from Activated Sludge of a Pharmacy Wastewater Treatment Unit - Mahsa Sedighi; Simin Nasseri (Biological Journal of Microorganism, 2019)
Introduction: Synthetic estrogen, 17α-ethinylestradiol (EE2), has adverse effects on aqueous environments even at the lowest concentrations. Identification of microorganisms with high degradation capability has always been expected. Biodegradation processes may involve the action of different microorganisms and microbial consortia, during which, either pollutants are consumed for growth or transformed due to co-metabolism. In this study, an enrichment culture of activated sludge from the pharmacy wastewater treatment unit was used for degradation of EE2 as the sole source of carbon and energy. Material and method: For obtaining the strains with the capability of EE2 degradation, the sludge samples were used as seed and the enrichment culture was performed using mineral salt medium (MSM) with EE2 as the sole carbon source. To evaluate the EE2 degradability of the mixed culture, EE2 was added to the cultures at initial concentrations of 0-4 mg L-1. The degradation rate of EE2 (using HPLC) and the biomass concentration (using spectrophotometry) were monitored during the biodegradation process and the kinetic results were also investigated. Results: Two colonies were obtained from the enrichment culture solution of activated sludge. It was concluded that the obtained mixed culture was able to degrade EE2 at different initial concentrations. Considering the probability of presence of multi-enzymes systems in the mixed culture which exhibit the property of cooperativity, the allosteric sigmoidal model was matched with the experimental data. The concentration of biomass was clearly increased along with EE2 biodegradation. The Monod growth equation was applied for modeling the variations of biomass concentration. Discussion and conclusion: In this study a mixed culture capable of degrading EE2 as the sole carbon and energy source was isolated from the activated sludge of the pharmacy wastewater treatment unit. EE2 was used as a growth substrate due to the increase in the cell population.